Wine production from different species of seaweed. - Benosa,Sophia Grace Olympia (2009.)
This study specifically aimed to test and compare the wine production of Gracilaria verrucosa, Kappaphycus alvarezii, and Kappaphycus striatum based on the physicochemical evaluation. The best seaweed wine produced was also determined through sensory evaluation.
Thesis (Understanding, Bachelor of Science in Biology ) College of Arts and sciences University of the Philippines Visayas, Miag-ao, Iloilo.
Keywords: Seaweed